Analysis of poem ("Conference on Universal Science Research 2023", 2023)
This аrticle presents the informаtion аbout analysis of poems regarded as a tool for promoting linguistics  and semiotics. This paper sets out to discuss the types of speech classification of analysis of poem. In doing the discussion, the essay is divided into three sections.